Análisis e interpretación de los estados financieros como herramienta para la evaluación de la gestión financiera de la empresa - Castro Tamayo, Verónica Valeria (2015)
This investigation project allows to accomplish with the created objectives that references to achieves an analysis and interpretation of the Financial statements applying indicators in order to know the real economic-financier situation of the Decorpisos limited company in Machala city. Into periods 2013 - 2014. And let the respective summary with the recommendations that will contribute to improve the company financial management. The methodology used for this task develop was the quantitative focus, descriptive level, no experimental design. Using besides the bibliographic - documental technique to analyse conceptualizations and authors criteria as a theorist base for this investigation, the field technique doing interviews to the manager and accountant and the observation of the company accounting processes in order to compile necessary information of the company to apply the procedures of the financial analysis. After of apply the analysis and interpretation of the financial statements. It got to the conclusion about Decorpisos limited company, ceramics and buildings marketing company is not generating sufficient liquidity to accomplish with its short-term obligations and maintain sufficient working capital, this due to that the average collection period is bigger than the providers payment, echoing this in the company indebtedness with third parties. Advice to the company to achieve an analysis and interpretation of its annual financial statements in order to determine adverse situations for the company and make decisions to benefit the improvement of its rentability.